2010
DOI: 10.3122/jabfm.2010.02.090091
|View full text |Cite
|
Sign up to set email alerts
|

Parental Acceptance of a Mandatory Human Papillomavirus (HPV) Vaccination Program

Abstract: Objectives: The objective of this study was to determine factors that influence parent's acceptance of a mandatory school-based human papillomavirus (HPV) vaccination program.Methods: A convenience sample of 325 parents, with children aged 9 to 17 years old, completed a 53-item survey. Survey questions targeted their opinions about HPV, the HPV vaccine, and a mandatory HPV vaccination program.2 tests were used to examine relationships between survey items. Results: Characteristics of parents who believed the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…In the Ferris et al (2010) study on parental acceptance of a mandatory human papillomavirus vaccination programme found that parents with a personal history of HPV infection or genital warts and greater familiarity with the adverse consequences of HPV infection were positive to the school-based vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…In the Ferris et al (2010) study on parental acceptance of a mandatory human papillomavirus vaccination programme found that parents with a personal history of HPV infection or genital warts and greater familiarity with the adverse consequences of HPV infection were positive to the school-based vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Constantine and Jerman (2007) found that most parents wanted to vaccinate their children by the 13 years of age, but some would not consider such vaccination before their children reach 16 years of age. Other studies have shown that parents were more likely to accept the vaccine if they had an older daughter in her late teens (Ferris, Horn, & Waller, 2010;Marlow, Waller, & Wardle, 2007a, 2007b.…”
Section: Demographic Factorsmentioning
confidence: 96%
“…Some authors reported that Hispanic and black individuals have a higher rate of negative attitudes towards immunization than white individuals [31][32][33], while other studies showed that the Caucasians are less likely to support the uptake of the vaccines than parents of other races and minor ethnicities [34][35][36]. No correlation between race and parental vaccine acceptance was found in other studies [37][38][39]. Nevertheless it is reasonable to suppose that different socio-cultural attitudes towards vaccination and a different perception of risk of catching a disease are often seen in different populations and might influence vaccination choices; however the reasons why differences exist between racial ethnic groups remain largely unknown [40].…”
Section: The Role Of Parentsmentioning
confidence: 99%